Perception Gaps of Disclosure of Patient Safety Incidents Between Nurses and the General Public in Korea. Issue 8 (9th December 2021) - Choi, Eun Young; Pyo, Jeehee; Lee, Won; Jang, Seung Gyeong; Park, Young-Kwon; Ock, Minsu; Lee, Haeyoung
Abstract : Objectives: This study aimed to explore nurses' perceptions regarding disclosure of patient safety incidents. Methods: An anonymous online survey was conducted, and results were compared with those of the general public using the same questionnaire in a previous study. Results: Among 689 nurses, 96.8% of nurses felt major errors should be disclosed to patients or their caregivers, but only 67.5% felt disclosure of medical errors should be mandatory. In addition, 58.5% of nurses were concerned that disclose will increase the incidence of medical lawsuits. More than two-thirds of nurses felt such discloses will reduce feelings of guilt associated with a patient safety incident. Only 51.1% of nurses, but 93.3% of the public, felt near misses should be disclosed to patients. Conclusions: Nurses generally had a positive attitude toward disclosure of patient safety incidents, but they preferred it less than the general public. To reduce this gap, legal and nonlegal measures will need to be implemented. Furthermore, it is necessary to continue monitoring the gap by regularly assessing perceptions of disclosure of patient safety incidents among health care professionals and the general public.